Nonlinear plasmonic nanohybrids as probes for multimodal cell imaging and potential phototherapeutic agents. (6th February 2019) - Boksebeld, Maxime; Kilin, Vasyl; Taitt, Rachael; Bonacina, Luigi; Géloën, Alain; Lysenko, Vladimir; Chevolot, Yann; Monnier, Virginie
Abstract: Silicon carbide (SiC) nanoparticles were coated with gold nanorods to prepare nonlinear plasmonic nanohybrids. Their structural properties were evaluated by Transmission Electron Microscopy. Nonlinear optical properties of the two components (second harmonic generation for SiC nanoparticles, two-photon luminescence for gold nanorods) were simultaneously found into nanohybrids and spatially colocalized. Photothermal effect was observed for nanohybrids. The cytotoxicity of nanoparticles, nanorods and nanohybrids towards healthy and cancer cell lines was then evaluated. SiC nanoparticles and nanohybrids showed no cytotoxicity for healthy cells while gold nanorods were found to exhibit an increasing toxicity with increasing concentrations, which was related to the presence of CTAB surfactant on their surface. Finally, nanohybrids exhibit toxicity for cancer cells and this effect was increased under laser irradiation at 808 nm, which matches the plasmon resonance of gold nanorods.